2022
DOI: 10.1186/s12903-022-02644-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an integrated model of oral health-promoting schools in improving children's knowledge and the KAP of their parents, Iran

Abstract: Introduction The aim of our study was to investigate the effect of an Oral Health Promoting School (OHPS) model on children's oral health in Iran. Methods This interventional quasi-experimental study was conducted in the academic year 2019–20 among 354 primary school students and their parents. A questionnaire including 17 questions was distributed among children before and 5 months after the program (The ranges of possible scores = 0–17). Training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Regarding intervention integrity, all the studies provided details on the theoretical basis, intervention frequency, compliance, and methods of follow-up contacts for participants. Two studies did not assess the consistency of interventions [ 19 , 22 ], and the rest did not provide a clear explanation on this matter. Two studies mentioned the possibility of contamination [ 18 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding intervention integrity, all the studies provided details on the theoretical basis, intervention frequency, compliance, and methods of follow-up contacts for participants. Two studies did not assess the consistency of interventions [ 19 , 22 ], and the rest did not provide a clear explanation on this matter. Two studies mentioned the possibility of contamination [ 18 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study reported that the education positively influenced students’ awareness, knowledge, and attitudes. However, the impact of social media as an individual factor was not separately assessed in this study [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past years, there has been an ascending increase in the number of tooth decays [ 4 , 5 ] and the prevalence of periodontal diseases [ 6 , 7 ] in Iranian children. On average, Iranian school-aged children of 6–7 years of age and 12-year-olds experienced 4.3 and 1.6 decayed teeth in 2004, respectively.…”
Section: Introductionmentioning
confidence: 99%